Characterization of Phytophthora nicotianae isolates from tobacco plants (Nicotiana tabacum) in Colombia - Vanegas, Diana Marcela; Angel Navarro, Rafael; Alfanador, Lucia; Gutierrez, Jaime Andres; Gonzalo Morales, Juan; Gaviria, Bertha Miryam (Revista Ceres, 2022)
The black shank disease caused by Phytophthora nicotianae causes losses in tobacco crops up 100%. In Colombia, P. nicotianae populations are poorly known causing wrong diagnostics and erratic management. Amplification of the Ypt1 gene and morphological characteristics of colonies, sporangia, chlamydospores and hyphae were used to identify P. nicotianae isolates. Races were identified according to the reaction induced by each isolate on the differential tobacco varieties Hicks, L8, KY 14 x L8 and NC 1071. As results, 71 isolates of P. nicotianae were identified and classified by races. Colonies of P. nicotianae were of white color, cottony and fluffy texture with smooth, non-swollen hyphae; spherical papillae with an average of 1.26 ìm and non-papillated and intercalary chlamydospores of medium size of 1.02 ìm that are typical characteristics of P. nicotianae. A species-specific PCR-amplified band of 389 bp was detected in all isolates tested. The presence of races 0,1 and 3 of P. nicotianae were determined in the Colombian departments of Huila and Santander. To the best of our knowledge, this is the first report of physiological races 0,1 and 3 of P. nicotianae in Colombia. Results are of relevance for disease management and tobacco breeding.